Constructing an alternative language: Historical revision in the fiction of Bessie Head - Kelly, Kristine N (Department of English Language and Literature, 2016)
Through consideration of Bessie Head's fiction and essays, the paper that follows investigates Head's use of fiction to challenge the hegemony of South African history, a history that fails to represent black South Africans except as "objects of abuse and exploitation" (Head, A Woman Alone 66). The absence of a subject position in history for black South Africans betokens a need for critical reevaluation of the structures and language of that history. History should document and create a people's identity; however, Head contends that South African historical discourse has obliterated the historical identity of black South Africans. The imaginative freedom that fiction allows provides Head with a radical means for reinscribing an alternative historical identity. Through four interrelated sections, then, this paper describes and evaluates the way in which Head's works challenge existing historical discourse by working through literature to establish an alternative set of historical structures. The Botswana land, offers Head, a space for experimentation with writing styles that evade reproducing an account of historical oppression and also for the practical construction of a new world. This construction includes agricultural reform that would give power over the forces of production to the workers of the land and which would in turn provide these workers with both economic and spiritual independence. The novels, however, display an incongruous duality wherein the construction of Head's new world is interfered with by the dominating voice of South African history. Hence, the subject and the problem of the novels becomes a conflict for the authority of history. Head's efforts towards constructing a new world also seek to implement women as a primary labor force in both material and creative production, thereby further challenging a history that has rendered women as sexual commodities. The Collector of Treasures offers a culmination of this conflict. Here, Head offers a strategy of narrative fragmentation interrelated with a dialogic, multi-voiced discourse that dismantles the single-voiced structure of a history determined by the politics of repression. Fiction offers a freedom of structure and thought unavailable to the historian; therefore fiction transgresses the boundaries created by a repressive history and is able to establish an original and self-sustaining historical world.